Current events in Cordel: popular language and journalistic support (Revista Internacional de Folkcomunicação, 2021)
It is observed that popular culture has long been the object of study by various researchers and social actors, especially at this time of pandemic, where popular culture is understood as creation and sociability, popular culture and life. For Beltrão (1980), culture is pre-existing, passes through our experience and criticism, and leads us to build a better world, according to the natural order that life requires. Therefore, our focus will be to present the importance of cordel literature, as an informative tool used for a long time by various social layers and which is still abundantly present today. Our study considers Cordel Literature to be a strong means of communication, especially in Northeast Brazil, the voice of a popular segment, which is configured as a process of folkcommunication and folkmedia. The literary, in its specificity, according to Marques de Melo (2008), is both entertainment and the means and support for the dissemination, conservation, transformation and updating of the people's culture. That is how Gilmar de Carvalho developed his work for over 40 years as a teacher, researcher and cultural producer, to whom we pay homage; bringing this secular expression and its creators that conserve strength and permanently feed informational flows as journalistic support.